Stereotactic Brainstem Biopsy in a Patient with Coagulopathy of Unclear Etiology: Case Report - Beynon, C.; Hoffmann, T.; Wick, W.; Unterberg, A. W.; Kiening, K. L. (min - Minimally Invasive Neurosurgery, 2011)
Parenchymal hemorrhage is one of the most feared risks of stereotactic brain biopsies potentially resulting in neurological deficits or even a fatal outcome. Patients with disorders of the coagulation system are at particular risk, so identifying these is one of the main tasks prior to surgery. Some patients may have a bleeding tendency despite normal laboratory values of the hemostatic system.We report the case of a patient with coagulopathy of unclear etiology undergoing a stereotactic brainstem biopsy.A medication scheme with tranexamic acid and desmopressin effectively decreased the patient’s bleeding time in vivo and the procedure was carried out without complications.
Keywords: intracranial tumor; anaplastic astrocytoma; stereotaxy; presurgical planning; coagulopathy